Pengaruh Literasi Keuangan, Literasi Akuntansi, dan Literasi Digital terhadap Kinerja UMKM Subsektor Usaha Mikro di Kota Pontianak Tahun 2022 - Fadilah, Nadhifah Nur'aini (Jurnal KIAFE, 2024)
This study examines the effects of financial literacy, accounting literacy, and digital literacy on the performance of micro-enterprises in Pontianak City in 2022. The study employs a quantitative approach using primary data collected through questionnaires distributed to 100 micro-enterprise owners. The sample was determined using the Slovin formula and selected through non-probability sampling with a convenience sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling with SmartPLS version 4.0. The results show that financial literacy has a positive and significant effect on micro-enterprise performance, accounting literacy has no significant effect, and digital literacy has a positive and significant effect. The model explains 31.9% of the variation in micro-enterprise performance. These findings indicate that financial and digital capabilities are important resources for improving business performance, while accounting literacy does not directly contribute to performance in the context examined.